Distinct Lotus japonicus Transcriptomic Responses to a Spectrum of Bacteria Ranging From Symbiotic to Pathogenic - Kelly, Simon; Mun, Terry; Stougaard, Jens; Ben, Cécile; Andersen, Stig U. (Frontiers in Plant Science, 2018)
Lotus japonicus is a well-studied nodulating legume and a model organism for the investigation of plant-microbe interactions. The majority of legume transcriptome studies have focused on interactions with compatible symbionts, whereas responses to non-adapted rhizobia and pathogenic bacteria have not been well characterised. In this study, we first characterised the transcriptomic response of L. japonicus to its compatible symbiont, Mesorhizobium loti R7A, through RNA-seq analysis of various plant tissues. Early symbiotic signalling was largely Nod factor-dependent and enhanced within root hairs, and we observed large-scale transcriptional reprogramming in nodule primordia and mature nitrogen-fixing nodules. We then characterised root transcriptional responses to a spectrum of L. japonicus interacting bacteria ranging from semi-compatible symbionts to pathogens. M. loti R7A and the semi-compatible strain Sinorhizobium fredii HH103 showed remarkably similar responses, allowing us to identify a small number of genes potentially involved in differentiating between fully and semi-compatible symbionts. The incompatible symbiont Bradyrhizobium elkanii USDA61 induced a more attenuated response, but the weakest response was observed for the foliar pathogen Pseudomonas syringae pv. tomato DC3000, where the affected genes also responded to other tested bacteria, pointing to a small set of common bacterial response genes. In contrast, the root pathogen Ralstonia solanacearum JS763 induced a pronounced and distinct transcriptomic pathogenic response, which we compared to the results of the other treatments. This comparative analysis did not support the concept that an early defence-like response is generally evoked by compatible rhizobia during establishment of symbiosis.